Analisis Reduplikasi Dalam Wacana Berita Olahraga Pada Harian Kompas Sebagai Materi Pembelajaran Bahasa Indonesia Pada Siswa Kelas XI SMK Muhammadiyah Kartasura - Susanti, Ria; , Drs. Yakub Nasucha, M.Hum (2016)
This study aims to 1) describe the reduplicated form in the discourse of sports news in Kompas daily as a matter of learning Indonesian in class XI student of SMK Muhammadiyah Kartasura, 2) describe the function of the use of reduplication in the discourse of sports news in Kompas daily as a matter of learning Indonesian in class XI SMK Muhammadiyah Kartasura. Object of research is the use of reduplication in sports news discourse in Kompas daily. Data were collected through technical log and see. The technique of analysis data using agih method with the continous technique re-engineering and change intentions. The results of this study, 1) reduplicated form, (a) repetition over without variation of phonemes, (b) repetition portion, (c) the repetition with affixation, and (d) repetition with variation phoneme/the sound changes, 2) functions reduplication found in this study, the noun form the noun, the verb formof verbs, adjectives form adverbs, verbs forming adverbs, noun formed numeralia, the noun form verb, figurative form adjectives, verb to form adjectives, adjective form of verbs, numeralia forming adverbs, nouns to form adjectives, and adverbs into adverbs. The conclusion of this study, it was found 4 form of reduplication and 12 function reduplicated in sports news as learning Indonesian. Keywords: reduplicated form, function reduplication, sports news